Post-war strategy Itzling. A methodological approach. - Karnutsch, Markus; Netsch, Stefan; Reiter, Thomas (Springer, 2018)
Post-war neighborhoods all over Europe are facing various kinds of challenges in order to adapt them for use in the future. The predominant factor in many concepts of neighborhood refurbishment is the energy demand of the buildings. In connection, many research projects focus on the reduction of CO2 emissions, omitting the fact that this specific value does not have any immediate benefit for the residents themselves, neither on the psychological nor on the economic level. The sole positive effects can be found on the macroeconomic level, which rarely is calculated and most likely cannot be communicated as a benefit to the residents in a comprehensible fashion. This approach may lead to considerable resistance among the residents against ambitious redevelopment plans. The methodological approach presented in this paper reflects the establishment of a vision for a neighborhood-development strategy. Its core is an iterative process using the tools of questionnaires, workshops and focus-group discussions, which involves the owners of the buildings, the local energy provider, policy makers, representation of the residents and research experts. The methodological framework was developed based on the reference neighborhood Itzling, which is situated in the city of Salzburg/Austria. It is an urban area with mostly social housing erected between 1966 and 1976, which houses approximately 2500 inhabitants. The singular priorities of this neighborhood's refurbishment plans were harmonized in the form of a questionnaire and multiple workshops. As a result of this process, five key areas of action - energy, living space, open space, social and mobility - were identified. The developed iterative process is multipliable and transferrable to comparable urban areas that share a set of similarities. It is the basis for future decisions and gives orientation to the building owners, the energy provider and policy makers. Besides the methodology, the outcomes of this process are a poster, a folder and a detailed catalog of measures. The poster and the folder visualize the neighborhood development strategy. A set of characters, icons and photos including easily comprehensible comics was developed. These design features are important in order to create a recognition value and to stimulate acceptance among the inhabitants of the neighborhood. Moreover, the low-threshold approach of the design facilitates future communication with the concerned public. The described methodology of the neighborhood-development strategy guarantees the inclusion of all stakeholders and supports a prioritization of future measures that can lead to a more energy-efficient and livable development of neighborhoods in need of adaptation.
Keywords: Wohngebiet; Modernisierung; Energetische Sanierung; Energieverbrauch; Mieter; Beteiligung; Kommunikation; Wohnumfeld